2011
DOI: 10.1037/a0024310
|View full text |Cite
|
Sign up to set email alerts
|

The shape of action.

Abstract: How do people understand the everyday, yet intricate, behaviors that unfold around them? In the present research, we explored this by presenting viewers with self-paced slideshows of everyday activities and recording looking times, subjective segmentation (breakpoints) into action units, and slide-to-slide physical change. A detailed comparison of the joint time courses of these variables showed that looking time and physical change were locally maximal at breakpoints and greater for higher level action units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
144
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(166 citation statements)
references
References 29 publications
22
144
0
Order By: Relevance
“…It was hypothesized that if participants differentiated between boundaries and nonboundaries, the length of time that they spent on each type of chord would differ. It was found that participants spent more time on boundary chords than nonboundary chords, which is consistent with previous work using dwell YOUNG CHILDREN PAUSE ON PHRASE BOUNDARIES 23 time methods for studying musical boundaries in adults as well as for action segmentation (Hard et al, 2011;Meyer et al, 2011).…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…It was hypothesized that if participants differentiated between boundaries and nonboundaries, the length of time that they spent on each type of chord would differ. It was found that participants spent more time on boundary chords than nonboundary chords, which is consistent with previous work using dwell YOUNG CHILDREN PAUSE ON PHRASE BOUNDARIES 23 time methods for studying musical boundaries in adults as well as for action segmentation (Hard et al, 2011;Meyer et al, 2011).…”
Section: Methodssupporting
confidence: 80%
“…They are not given any instructions for how to time their key presses and they experience the sequence as it unfolds. The dwell time method has previously been used to YOUNG CHILDREN PAUSE ON PHRASE BOUNDARIES 10 investigate action segmentation, showing that participants "dwell" (spend relatively more time on) slides depicting event boundaries (Hard, Recchia, & Tversky, 2011). Preliminary work has found converging results with preschoolers and infants (Meyer, Baldwin, & Sage, 2011;Sage, Ross, & Baldwin, 2012).…”
Section: Young Children Pause On Phrase Boundariesmentioning
confidence: 85%
“…All pairwise comparisons were 13 significant: dwelling was greater for fine than non-boundaries (t(13) = -2.475, p < .0167), greater 14 for coarse than fine boundaries (t(13) = -3.749, p < .01), and greater for coarse than non-15 boundaries (t(13) = -3.819, p < .01). In the original dwell time study for action segmentation (Hard et al, 2011), it was found 9 that participants who looked longer at boundaries recalled more actions from the slideshow. The …”
mentioning
confidence: 99%
“…In addition, studies, e.g. by Hard et al [8], have shown that the amount of information contained in a video sequence around breakpoints depends on the action granularity of the corresponding breakpoints, with breakpoints associated with coarser action units carrying more information than breakpoints associated with finer units. Interestingly, the concept of granularity has received little attention in the context of video annotations [17,19] despite their high significance for visual cognition.…”
Section: Introductionmentioning
confidence: 99%